Teacher Development Programs in Language Education: AI-Driven Linguistic Perspectives on Effective Practices - Chokkappagari, Rishitha (Universitas Kristen Immanuel, 2025)
AI today is progressing very fast in the treatment of different fields and touches almost all sectors, and education is one of them. AI is thus growing dear to language education for the ability it holds towards transforming the teaching approaches as well as the teacher training programs. This paper, Teacher Development Programs in Language Education: ‘AI-Driven Linguistic Perspectives on Effective Practices’, provides an extensive overview of the ways through which the integration of AI, into the professional development of language teachers can be successful. The text starts the theoretical framework of language education that is the theories of language, educational psychology, and the sociocultural approach to language education. The function of AI is then brought to focus by explaining a brief history of AI use in education, a current state of integration in educational process, and its prospective advancements. This paper revolves around the concept of AI teacher development programs designs and execution. For each strategy, it provides detailed conversations on the ways in which AI can be implemented when it comes to curriculum mapping, student differentiation, and instructing. It also elaborates groundbreaking and imaginative ways of AI in pronunciation, speaking, reading, and writing improvement. This paper provides the higher education, and private language schools’ case studies that explain how AI is implemented in practice to enhance teacher professional growth and development outcomes. Also, the paper discusses some of the core problems of big data like data privacy, algorithmic bias, and availability, and ways on how to deal with these problems responsibly are provided. Hence, the analysis and positive feedback from the programmes implementing the use of AI in the training of teachers through the rates of student performances, supplemented by the feedback from the teachers themselves, make the book informative on the impacts, as well as the shortcomings of AI in this area of practice. It ends by identifying future research directions based on the challenges raised in this paper, stressing on the roles of research, policy, and partnership to push forward language education with AI.